TEACHER TALK IN CLASSROOM INTERACTION - Nurpahmi, Sitti (ETERNAL (English, Teaching, Learning, and Research Journal), 2017)
This paper explains about the types of teachers’ talk in classroom interaction. This research was case study. In this research, the writer applied Descriptive Research Design which applied observation method. It aimed to gain the data that were observed during Teaching and learning process. The data were presented by analyzing the teacher talk and the speech act used by the informant. The source of data was the lecturer of ICP FMIPA UNM Makassar. The instrument of this study was observation where the writer used video cam to record and shoot the speech of the lecturer and also transcribing it. This research instrument was applied to acquire the data about teacher talk and speech act used by the lecturer at ICP FMIPA UNM Makassar. The result of the research shows that there are some types of teachers’ talk performed by the lecturer during classroom interaction, they are greeting student, reviewing the previous material, introducing the new material, giving direction and instruction, encouraging and motivating, giving advice and closing the class.